POE (PREDICT,OBSERVE,EXPLAIN): EFEKTIVITAS MODEL PEMBELAJARAN TERHADAP HASIL BELAJAR PESERTA DIDIK - Chindy Aisahara; Deden Makbuloh; Muhammad Mustofa (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
This study was motivated by the low learning outcomes and critical thinking skills of students in Islamic Religious Education (PAI) at SMP Negeri 2 Krui, where instruction remains predominantly teacher-centered through the Direct Instruction model. This condition has resulted in limited student participation and difficulties in achieving higher-order cognitive skills (C6). The purpose of this study was to examine the effectiveness of the Predict, Observe, Explain (POE) instructional model in improving students’ learning outcomes in PAI. The study employed a quantitative approach using a quasi-experimental method with a post-test only control group design. The sample consisted of 64 eighth-grade students selected through cluster random sampling, comprising an experimental group that received instruction using the POE model and a control group taught through Direct Instruction. The research instrument was a validated multiple-choice test. Data were analyzed using normality and homogeneity tests, followed by the Mann–Whitney U hypothesis test. The findings indicated that the data were not normally distributed but were homogeneous; therefore, the nonparametric Mann–Whitney U test was applied. The Asymp. Sig. (2-tailed) value of 0.000 (< 0.05) revealed a statistically significant difference between the two groups. In conclusion, the POE model proved to be more effective than Direct Instruction in enhancing students’ learning outcomes in PAI, as it promotes active engagement, deeper conceptual understanding, and the development of critical thinking skills.